Development of STEM-based Descriptive Statistics Course Modules to Improve Mathematical Literacy - Chasanah, Aprilia Nurul; Adna, Syita Fatih; Ibrahim, Joko; Gunawan, Gunawan (FKIP Universitas Lampung, 2024)
Abstract: Mathematical literacy skills are very necessary so that students are able to face educational challenges in the cognitive aspect. One thing that has characteristics to answer the demands of 21st century learning is STEM. This study aims to develop a stem-based Descriptive Statistics course module using book creators to improve mathematics literacy skills with good quality that meets valid, practical, and effective. This research is development research using the Plomp model which consists of an initial investigation phase; design phase; realization/construction phase; test, evaluation, and revision phases; and implementation. The subject of this study is a student of the Mathematics Education Study Program at Universitas Tidar for the 2022/2023 academic year. The research instruments used in this research were validation sheets, questionnaires, and research instruments. This module is designed and developed based on the needs of students. After being developed this module was validated by two experts who are competent in their fields. The results of the module validity assessment based on experts are valid with an average of 74.5 with good categories. The practical results are based on student assessments which have a percentage of 56.52% with excellent criteria and 39.13% with good criteria. The statistical significance test of the module is based on test results with a classical average of 92.25 and the percentage of students whose scores are above KKM (≥ 75) is 86.93%. The data analysis results using the Wilcoxon test show that there is an influence of using the STEM learning model on mathematical literacy with a p-value lower than 0.05. The STEM learning model improves the mathematical literacy abilities in the medium category (N-Gain = 0.3889).Therefore, this lecture module is suitable to be used as one of the learning resources for the Descriptive Statistics and meets the quality aspects of validity, practicality, and effectiveness. Keywords: module, descriptive statistics, book creator, mathematical literacy.DOI: https://dx.doi.org/10.23960/jpmipa/v25i1.pp116-126